The Mental Workload Of Nurses In The Role Of Nursing Care Providers - Witri Destiani; Ati Surya Mediawati; Ryan Hara Permana (Universitas Padjadjaran, 2020)
The responsibility of nurses as nursing care providers is a factor that affects the mental workload. The mental workload of nurses as caregivers who have to work and interact with patients professionally for 24 hours would arise. It may because of continuous adaptation of time constraints in providing nursing care for 24 hours, unclear job demands, limited ability, lack of motivation and mood, and the psychological burden of the nurse. This study aimed to describe the mental workload in carrying out their role as the nursing care provider at eight inpatient wards, Sumedang public hospital. This research applied descriptive quantitative design. The mental workload was measured using the NASA-TLX instrument. The samples were 94 who works inpatient rooms, they were randomly selected through cluster sampling techniques. Analysis of the data was descriptive analysis. The results of the study showed that 67% of nursing nurses had a mental workload that was in the role of providing nursing care. Nurses have a high mental workload in providing nursing care in special surgical wards (53.8%) and child wards (50%). It is recommended that hospitals evaluate the work system of nurses to examine the physical, psychological and behavioral changes that occur to nurses. It is expected that nurses show good performance in carrying out their role as nursing care providers.